Search for the associated production of a b quark and a neutral supersymmetric higgs boson that decays into τ Pairs - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; et al. (American Physical Society (APS), 2010)
We report results from a search for production of a neutral Higgs boson in association with a b quark. We search for Higgs decays to τ pairs with one τ subsequently decaying to a muon and the other to hadrons. The data correspond to 2.7fb-1 of pp̄ collisions recorded by the D0 detector at √s=1.96TeV. The data are found to be consistent with background predictions. The result allows us to exclude a significant region of parameter space of the minimal supersymmetric model. © 2010 The American Physical Society.